2021
DOI: 10.1371/journal.pone.0251944
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in people living with HIV-associated neurocognitive disorder: A scoping review study

Abstract: Quality of life (QoL) is recognized as an essential end point in the disease management of chronic conditions such as HIV with calls to include good QoL as a ‘fourth 90’ in the 90-90-90 testing and treatment targets introduced by World Health Organization in 2016. Cognitive impairments impact a broad spectrum of experiences and are a common issue effecting people living with HIV (PLWH). Despite this, few studies have examined QoL in PLWH who also have a cognitive disorder. This study aimed to synthesize and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 68 publications
(302 reference statements)
2
27
0
2
Order By: Relevance
“…This relationship has previously been described in the literature, 49–51 but our study has further contributed to the field, thus addressing suggestions of future research in this line. 48 As such, our article supports the relevance of evaluating the quality of life and interacting factors for PLWHIV. Our work also supports HIV advocacy groups that are calling for its inclusion as an additional 90 in the 90-90-90 testing and treatment target introduced by the World Health Organization in 2016.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This relationship has previously been described in the literature, 49–51 but our study has further contributed to the field, thus addressing suggestions of future research in this line. 48 As such, our article supports the relevance of evaluating the quality of life and interacting factors for PLWHIV. Our work also supports HIV advocacy groups that are calling for its inclusion as an additional 90 in the 90-90-90 testing and treatment target introduced by the World Health Organization in 2016.…”
Section: Discussionsupporting
confidence: 70%
“…The latter is recognised as a subjective and multidimensional well-being variable that involves an individual’s physical, mental, emotional, and social functioning, and is essential for the management of chronic diseases such as HIV. 48 , 49 According to a recent review, few studies have hitherto analysed the relationship between HRQoL and neurocognitive impairment in MSM with HIV. 48 Nevertheless, some previous studies have found that the presence of neurocognitive impairment is significantly associated with lower HRQoL scores in HIV-positive MSM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews lasted 45–97 min and were audio-recorded, transcribed verbatim and checked for accuracy. Interview guides based on a review of the HRQoL literature and experiences of PLWH with CI [ 29 ] were used to structure the interview. Questions were open-ended, and probing.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-NCI is a spectrum of disorders that can fluctuate over time and includes, but is not limited to, impaired executive function, working memory, and attention ( 2 ). People with HIV-NCI have a premature decline in overall physical and psychological health, with difficulties maintaining employment and social relationships and in performing instrumental activities of daily living ( 9 13 ). HIV-NCI is an independent risk factor for mortality, and currently, there are no effective treatments in the context of ART ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%